The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1248/yakushi.18-00156
|View full text |Cite
|
Sign up to set email alerts
|

Association between Elimination Half-life of Benzodiazepines and Falls in the Elderly: A Meta-analysis of Observational Studies

Abstract: Benzodiazepine receptor agonists (BZDRAs) have been associated with an increased risk of falls in the elderly. However, the association between the elimination half-life (t 1/2) of BZDRAs and the diŠerence between benzodiazepines (BZDs) and non-benzodiazepines (Z-drugs) has not been clariˆed. By conducting a meta-analysis of observational studies, we compared the risk of falls with respect to 1) short-acting BZDRAs (t 1/2 < 12 h) vs. long-acting BZDRAs (t 1/2 12 h) and 2) BZDs vs. Z-drugs in elderly patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…10,11 BZD/non-BZD is a risk factor for falls, cognitive impairment, and delirium. [12][13][14] It is reported that BZD/non-BZD could cause dependence within months, even with regular doses. 15 Additionally, another study reported that BZD/non-BZD can be reduced at a relatively high rate, discontinued, or switched to lemborexant, which is considered less risky.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 BZD/non-BZD is a risk factor for falls, cognitive impairment, and delirium. [12][13][14] It is reported that BZD/non-BZD could cause dependence within months, even with regular doses. 15 Additionally, another study reported that BZD/non-BZD can be reduced at a relatively high rate, discontinued, or switched to lemborexant, which is considered less risky.…”
Section: Discussionmentioning
confidence: 99%
“…BZD/non‐BZD is a risk factor for falls, cognitive impairment, and delirium 12–14 . It is reported that BZD/non‐BZD could cause dependence within months, even with regular doses 15 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of observational studies of older subjects aged ≥ 65 years previously suggested that benzodiazepine receptor agonists signi cantly increase fall incidence, regardless of the duration of drug action [15]. In older adults, blood levels of drugs may be increased because of the impairment of renal and hepatic function associated with physiological decline, which likely increases fall risk.…”
Section: Discussionmentioning
confidence: 99%
“…As triazolam has a very short half-life of 2.9 h and the effect of carry-over to the next morning is considered small, it tends to be more commonly used on the elderly compared with long-acting benzodiazepines. However, it has also been reported that the occurrence risk of falls is the same regardless of half-life, or the presence or absence of a benzodiazepine skeleton [40]. Thus, there is no consensus on the effects of factors such as half-life on falls.…”
Section: Discussionmentioning
confidence: 99%